FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING PADA PERUSAHAAN KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2015-2017 - Siti Kholipah; Dhini Suryandari (UNIB Press, 2019)
This study aimed to examine the effect of audit opinion, audit fee, and KAP size on auditor switching with companies size as moderating variable. The population in this study were 86 financial companies listed on Indonesia Stock Exchange in 2015-2017. The purposive sampling technique produced 47 companies as the sample. This study used secondary data with the documentation method and analyzed using logistic regression as well as absolute difference test value to test the moderating variable. The results of this study showed that audit opinion has negative significant effect on auditor switching, KAP size has positive significant effect on auditor switching, and audit fee has not effect on auditor switching. Company size is not able to moderate the influence of audit opinion, audit fee, and KAP size on auditor switching. The conclusion of this study is the companies that conduct auditor switching are influenced by the opinions received and the KAP size. Audit fee does not affect the company's decision to conduct auditor switching and the size of the company is not a determinant of the auditor switching.Keywords: Audit Opinion; KAP Size; Auditor Switching